A First Report of Infestation by Pseudolynchia canariensis in a Herd of Pigeons in Shahrekord (Southwest of Iran) - Khodadad Pirali-Kheirabadi; Amir Dehghani-Samani; Nader Ahmadi-Baberi; Vida Najafzadeh (Tehran University of Medical Sciences, 2016)
Background: Pigeons (Columba livia) have been kept as pet and reared for food in several countries including Iran. Ectoparasites are regarded as the basic causes of retardation in growth, lowered vitality and poor conditions of the birds. Pseudolynchia canariensis a hippoboscidae fly is one of the important ectoparasites of pigeons and is responsible for the transmission of pathogens to birds and humans same as pathogenic protozoan Haemoproteus columbae. Methods: A herd of domestic pigeons contained 50 pigeons in Shahrekord, southwest Iran was evaluated clinically infested by ectoparasites. Ectoparasites were removed. The samples were collected and then referred to the Laboratory of Parasitology of Shahrekord University, Shahrekord, Iran. Results: Usin diagnostic key for diptera fly, these flies were find P. canariensis. This is a rare report of infestation of pigeons herd by P. canariensis in Iran. The infestation rate was 40% that rate of infestation in pipers was more than females and in females was more than males. Conclusion: The rate of infested pipers was more than adults that maybe the less potential of pipers in removing of ectoparasites is reason of this higher rate.